2003
DOI: 10.1111/1467-9280.t01-1-01412
|View full text |Cite
|
Sign up to set email alerts
|

On Wildebeests and Humans

Abstract: On the basis of a functional perspective, we hypothesized that negative stimuli are detected faster than positive stimuli. In Experiment 1, participants were subliminally presented with positive and negative words or with no words at all. After each presentation, participants were asked whether they had seen a word. They detected negative words more accurately than positive words. In Experiment 2, participants were subliminally presented with negative or positive words. After each presentation, they were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(68 citation statements)
references
References 29 publications
3
63
2
Order By: Relevance
“…In contrast, stimulus-driven control over attentional resources can be seen as “hot”, indifferent to task demands, and effortless insofar as stimulus processing is “automatically” carried out to completion without conscious monitoring (Tzelgov, 1997). Such control is vital for rapid and preconscious appraisal of stimuli that have social, biological, or survival importance (e.g., emotional expressions on faces; Bargh, 1989; Dijksterhuis & Aarts, 2003; Eastwood, Smilek, & Merikle, 2001; Okon-Singer et al, 2007; Yantis, 2000). Though emotional stimuli may be task-irrelevant, they have the intrinsic potential to disrupt task-driven cognition by automatically absorbing attentional resources and reducing working memory capacity.…”
mentioning
confidence: 99%
“…In contrast, stimulus-driven control over attentional resources can be seen as “hot”, indifferent to task demands, and effortless insofar as stimulus processing is “automatically” carried out to completion without conscious monitoring (Tzelgov, 1997). Such control is vital for rapid and preconscious appraisal of stimuli that have social, biological, or survival importance (e.g., emotional expressions on faces; Bargh, 1989; Dijksterhuis & Aarts, 2003; Eastwood, Smilek, & Merikle, 2001; Okon-Singer et al, 2007; Yantis, 2000). Though emotional stimuli may be task-irrelevant, they have the intrinsic potential to disrupt task-driven cognition by automatically absorbing attentional resources and reducing working memory capacity.…”
mentioning
confidence: 99%
“…One recent line of study examined whether the emotional valence of words could be accessed nonconsciously. In a recent publication, Dijksterhuis and Aarts (17) showed that masked negative words could be categorized as negative above chance level, in contrast with positive words, even if subjects could not guess the meaning of the words. However, these results could be interpreted, at least in part, in terms of a systematic response bias that could not be ruled out in the absence of such detection measures as dЈ (18).…”
mentioning
confidence: 99%
“…Word recall studies have shown that recall of emotional words is greater to that of neutral words, independently of whether words are semantically related or not (Ferr e, Fraga, Comesaña, & S anchez-Casas, 2014). Other techniques, such as Rapid Visual Serial Presentation (Anderson, 2005) and priming (Dijksterhuis & Aarts, 2003), have revealed effects related to the detection and recognition of emotional words using a length presentation of up to 13.3 ms. On balance, these findings show that emotionality is a complex issue, and that even though both pleasant and unpleasant words (i.e., words with high arousal ratings) are different from neutral ones, they are also different from each other.…”
Section: Emotional Words and The Two Dimensional Models Of Emotion: Bmentioning
confidence: 99%
“…Usually, these differences in the processing of emotional stimuli appear in later components, such as P200 Wang et al, 2013) or the Early Posterior Negativity (Citron, 2012;Scott et al, 2009). However, early differences have been reported in studies which used emotional words, be they behavioral, such as priming studies with pleasant and unpleasant words at a 13.3 ms presentation rate (Dijksterhuis & Aarts, 2003), or electrophysiological, which, as in our experiment, showed modulations in the amplitude of early components, such as P1 (Bernat et al, 2001;Scott et al, 2009;Wong et al, 2004) or N1 (Bernat et al, 2001;Hofmann et al, 2009). It is important to add that these electrophysiological studies used high arousal negative words, either as the only experimental condition or together with another condition which contained pleasant words.…”
Section: N1 and The Pleasantness Effectmentioning
confidence: 99%